Defining the Great Lakes Passenger Freight Propeller: A Statistical, and Historical Study - Mihich, Martha (East Carolina University, 2018)
Passenger freight propellers were integral to the Great Lakes economy for nearly 100 years. A unique vessel type created for a unique need, shipbuilders combined different new technologies to create faster, more efficient, and more comfortable ships. This thesis explores the technical development of the passenger freight propeller using statistics, and comparisons to the historic record. Since ship design is a complex process, involving numerous considerations, multivariate linear regressions were determined to be the best fit. From these techniques, a more nuanced view of the passenger freight propeller emerged. While primary sources alone can provide important information about larger companies or maritime disasters, the ships or smaller companies were under-recorded. Utilizing ship registration data, the contribution of these smaller companies is more visible. After comparing the initial statistics, historical comparison answered some questions and provided some more. This thesis should be taken as a jumping off point for future research into this important Great Lakes ship.
Keywords: Propellers--History; Cargo ships--Great Lakes (North America) --Passenger traffic--History; Goodrich Transportation Company